Effect of Tailored Nursing Program on Selected Responses among Jordanian Patients with Lung Cancer - Hala Ramadan Mousa AL-Mawajdeh; Safaa M. Hassanein; Heba Ahmed Mohammed (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Health status affects patients with lung cancer due to disease symptoms, treatment side effects and overall physical limits. Tailored nursing care have an effective role in reducing intensity of symptoms and chemotherapy side effects. Aim: To investigate the effect of a tailored nursing program on selected responses (chemotherapy side effects) among Jordanian patients with lung cancer. Design: A quasi-experimental design (nonequivalent, pre-posttest control group). Tools: Tool (I): Demographic and medical data tools (DMDS). While Tool (II): Chemotherapy side effects worksheet. Setting: Amman, the capital city of Jordan. Al-Bashir Hospital, Hashemite Kingdom of Jordan, is in the Jabal Ashrafieh area of Al-Taj Street. The oncology department consists of 7 rooms for women, and 8 rooms for men knowing that each room equipped with 2 beds. Sample: A convenient sample over 6 consecutive months. 60 adult participants with a confirmed diagnosis of primary lung cancer. The sample was randomly assigned to the study and control groups, each of them was consisting of 30 participants. Results: Over a period of three weeks, the study revealed significant differences in chemotherapy side effects between study and control groups regarding fever, fatigue, nausea, and vomiting scores that decreased in the study group but worsened in the control group (p < 0.001). Mouth sores, diarrhea, constipation, loss of appetite, dysphagia, and edema were decreased in the study group, with opposite results in the control group (p < 0.001). Conclusion: A tailored nursing program was effective in reducing chemotherapy side effects among Jordanian patients with lung cancer. Recommendation: Establishing and development of tailored nursing program for patients with lung cancer to reduce intensity of chemotherapy side effects. Replicating the study to a large sample size from different types of cancer is recommended.